The Bills of Exchange Act, 1882 (45 & 46 Vict., c. 61) : an act to codify the law relating to bills of exchange, cheques, and promissory notes : with explanatory notes and index - Chalmers, M. D.; Great Britain (London : Waterlow, 1967)
The Bill of exchange Act, 1882, which codifies the law relating to Bills of Exchange, Cheques, and promissory notes was passed on the 18th of August, snd came into immediate operation.
Includes index and explanatory notes
ucj, 15/01/2019
Loans
Keywords: Bills of exchange; Negotiable instruments